Back to normal; serological testing for COVID‐19 diagnosis unveils missed infections. Issue 7 (25th March 2021) - Tsuchida, Tomoya; Nitahara, Yuko; Suzuki, Shotaro; Komase, Yuko; Candray, Katherine; Kido, Yasutoshi; Nakagama, Yu; Yamasaki, Yukitaka; Imamura, Mitsuru; Kawahata, Kimito; Kunishima, Hiroyuki; Fujitani, Shigeki; et al.
Abstract: Background: The gold standard for coronavirus disease (COVID‐19) diagnosis has been the detection of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNA by nucleic acid amplification testing (NAAT). On the other hand, serological testing for COVID‐19 may offer advantages in detecting possibly overlooked infections by NAAT. Methods: To evaluate seroconversion of NAAT‐negative pneumonia patients, immunoglobulin M (IgM) and IgG targeting the spike protein of SARS‐CoV‐2 were semiquantified by an immunofluorescence assay. Seroconversion was confirmed by another serological method, targeting the nucleocapsid protein. Results: Eight suspected but unconfirmed COVID‐19 pneumonia patients (median age, 39 years; range, 21–55) were included. The median period between symptom onset and NAAT sample collection was 6 days (2–27 days). None of them had tested positive for SARS‐CoV‐2 by NAAT. In contrast, all eight patients revealed seropositivity with the two serological methods, indicating actual seroconversion against SARS‐CoV‐2. The median period between onset and blood sampling was 26.5 days (7–51 days). Conclusion: Eight patients with COVID‐19 pneumonia, initially tested negative for SARS‐CoV‐2 by NAAT, were finally confirmed of the diagnosis by serological testing. To cover the whole spectrum of this heterogenous infectious disease, serology testing should be implemented to the multitiered diagnostic algorithm for COVID‐19.